Recent progress of mixed-linker Zn2+ metal-organic frameworks and their applications - Shamsulazri, Nur Amani Najwa; Saifullizan, Nurhidayah; Sabar, Sumiyyah; Raman, Velan; Ediati, Ratna; Yoshinari, Nobuto; Begum, Sharifa Zaithun; Md Yusof, Enis Nadia (Elsevier, 2025)
Metal-organic frameworks (MOFs) are regarded as a versatile class of porous materials, demonstrating widespread applications owing to their tunable structures and outstanding properties. Among MOFs, mixed-linker varieties containing Zn2+ ions, have emerged as promising materials with unique properties and versatile functionalities. The innovative approach has led to the development of MOFs with unique functional and structural features, making them promising candidates for various applications. This paper presents the latest five-year breakthrough in mixed-linker Zn2+ MOFs, highlighting their synthesis, structural diversity, and noteworthy properties. Additionally, it explores the diverse applications of these MOFs in environmental and energy fields, such as sensing, gas storage and separation, and electronic and electrochromic applications. The combination of mixed-linker systems and Zn2+ metal ions offers intriguing prospects for the future MOF research, with the potential to address critical challenges in various technological domains.